The Role of mediating perfectionism in relationship goal orientation with students' responsibility - Mohammad Norouzi; Abdolvahab Pourghaz; Afsaneh Marziyeh (مطالعات روانشناسی تربیتی, 2021)
The present research was conducted with the aim of investigating the relationship between goal orientation and students' responsibility through the mediation of perfectionism. The research method was descriptive-correlation. The statistical population of this research was all 3,903 boy students in the first grade of the second level of high school in Zahedan in the academic year of 2018-2019. Through multi-stage cluster random sampling method 351 students were selected and were studied through three questionnaires of Achievement Goal Questionnaire-Revised version (AGQ-R) (Elliot and Murayama, 2008), Positive and Negative Perfectionism (Terry Short et al., 1995) and the California Psychological Inventory Responsibility (CPI-RE) scale. The research results showed that the goals of tendency dominance and tendency performance have a positive and significant relationship with responsibility at 99% confidence level (P <0.01). Also, no significant relationship was found between avoidance dominance goals and avoidance performance with responsibility. The results of path analysis indicate that the goals of tendency dominance and tendency performance indirectly and with the mediation of positive perfectionism can have relationship with responsibility. The results also show that negative perfectionism plays a reverse mediating role in the relationship between avoidance dominance goals and avoidance performance with responsibility. Therefore, it can be concluded that the goals of tendency development impact on positive perfectionism, which this issue in turn will lead to students' responsibility.